2018
DOI: 10.1016/j.jcin.2017.09.034
|View full text |Cite
|
Sign up to set email alerts
|

1-Year Clinical Outcomes in Women After Transcatheter Aortic Valve Replacement

Abstract: Intermediate to high-risk women enrolled in this first ever all-women contemporary TAVR registry experienced a 1-year VARC-2 composite efficacy endpoint of 16.5%, with a low incidence of 1-year mortality and stroke. Prior revascularization and EuroSCORE I were independent predictors of the VARC-2 efficacy endpoint, whereas EuroSCORE I, baseline atrial fibrillation, and prior percutaneous coronary intervention were independent predictors of the 1-year death or stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…Prior coronary revascularisation (HR 1.72, 95% CI: 1.17-2.52; p=0.006) indicating established CAD and EuroSCORE I (HR 1.02, 95% CI: 1.00-1.04; p=0.027) were independent predictors of the VARC-2 efficacy endpoint. Of note, after adjustment, no significant association was observed between history of pregnancy or any sex-specific factors and one-year TAVR outcomes 38 . Finally, lower-risk patients are now a matter of debate and several trials are ongoing.…”
Section: Transcatheter Aortic Valve Implantationmentioning
confidence: 80%
“…Prior coronary revascularisation (HR 1.72, 95% CI: 1.17-2.52; p=0.006) indicating established CAD and EuroSCORE I (HR 1.02, 95% CI: 1.00-1.04; p=0.027) were independent predictors of the VARC-2 efficacy endpoint. Of note, after adjustment, no significant association was observed between history of pregnancy or any sex-specific factors and one-year TAVR outcomes 38 . Finally, lower-risk patients are now a matter of debate and several trials are ongoing.…”
Section: Transcatheter Aortic Valve Implantationmentioning
confidence: 80%
“…The Women’s International Transcatheter Aortic Valve Implantation (WIN-TAVI) Real-World Registry found that increasing age, history of prior stroke, left ventricular ejection fraction <30% and the generation of TAVI device deployed were all independent predictors of 30-day VARC-2 primary safety endpoint (a composite of all-cause mortality, stroke, major vascular complication, life-threatening bleeding, acute kidney injury, coronary artery obstruction and repeat procedure for valve-related dysfunction) in women. [48] In the effort to identify sex-specific factors that may influence outcomes, a history of pregnancy was found to be protective (OR 0.63). Age of menopause, history of osteoporosis and gynaecological or breast cancers seemed to have no influence on the primary safety endpoint.…”
Section: Gender-specific Analysismentioning
confidence: 99%
“…[29] The updated 1-year follow-up demonstrated a univariate but not multivariate protective association of previous history of pregnancy with 1-year incidence of death or stroke; also it failed to demonstrate any association with the VARC-2 composite efficacy endpoint beyond 30 days (a composite of all-cause mortality, all stroke, MI, hospitalisations for valve-related symptoms or worsening congestive heart failure or valve-related dysfunction). [48]…”
Section: Gender-specific Analysismentioning
confidence: 99%
“…Transcatheter aortic valve replacement (TAVR) has emerged as an effective treatment for aortic stenosis (AS) in moderate‐to‐high risk patients 1,2 . Despite significant advances in valve design and delivery techniques, TAVR remains associated with numerous complications such as paravalvular leak, stroke, and vascular access site bleeding 3‐5 . The majority of TAVR candidates are elderly patients with pre‐existing comorbidities that offset the procedure's long‐term prognosis 6 .…”
Section: Introductionmentioning
confidence: 99%